Giant fungal gastric ulcer in an immunocompetent individual - Praveer Rai; Sunil B Chakraborty (The Saudi Journal of Gastroenterology, 2012)
Candida infection of gastrointestinal tract is frequent in immunocompromised patients and rare in an otherwise healthy person in whom no permissive factor is present. Herein is a case report on 25-year-old woman, 2 months postpartum, with fungal gastric ulcer with invasion leading to fungemia. She developed fever and anemia. Gastric biopsy and blood culture both showed growth of Candida albicans. The patient responded well to parenteral amphotericin B. This supports the hypothesis of invasion of Candida from gastric ulcer into blood.